Answer:
y=3/2x+1
Step-by-step explanation:
y-4= -⅔(x-6)
y-4=-⅔x+4
y=-⅔x+4+4
(equation of line 1) y= -⅔x+8 gradient= -⅔
(line 2)gradient=3/2
note* the gradients of perpendicular lines multiplied result to -1
gradient=<u>y²-y²</u>
<u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u><u> </u>x²-x¹
<u>3</u><u> </u>=<u>y</u><u>+</u><u>2</u>
<u> </u><u> </u>2. x+2
multiply both sides by 2(x+2)to remove the denominators
3(x+2)=2(y+2)
3x+6=2y+4
3x+6-4=2y
3x+2=2y
divide all sides by 2
3/2x+1=y
y=3/2x+1
Answer:मन्दिर एक भवन हो जुन मानिसहरु देवताहरु को पूजा वा अन्य धार्मिक प्रयोजनहरु को लागी प्रयोग गर्दछन्। धेरै प्राचीन धर्महरुमा पूजा घरहरु मन्दिरहरु भनिन्थ्यो। हिन्दू धर्म, बौद्ध धर्म, र धेरै अन्य धर्महरु आज मन्दिरहरु छन्। वास्तुकला, वा मन्दिरहरु को निर्माण शैली, ठाउँ बाट ठाउँ फरक हुन्छ।
mark me as brainliest if this helps to u
Answer:
see below
Step-by-step explanation:
For the HL theorem to be applicable, the hypotenuses must be the same length:
x+3 = y-1
and the marked legs must be the same length:
y-3 = 2x-1
__
Recognizing y-3 = (y-1) -2, we can substitute into the second equation using the first equation:
(y -1) -2 = 2x -1
(x +3) -2 = 2x -1 . . . substitute for y-1
2 = x . . . . . . . . . . add 1-x to both sides
Then the first equation tells us ...
x+4 = y = 2+4 = 6
The values of x and y are ...
x = 2, y = 6
Answer:
Step-by-step explanation:
nth term means an expression which allows us to find the term that is in the nth position in the sequence.
Hope this helps
plz mark as brainliest!!!!!!!!!
The answer to this is 3.5